(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
The Sediment microbial Fuel Cell (SMFC) has been studied in terms of electrical power generation, and water treatment. With the aim to design the Sediment Microbial Fuel Cell (SMFC), the sediment was brought from the Al-sonobar River bed, where it was described to indicate the organic content and nutrients in it. The cell was equipped with a surface aeration system and started working in it. Where it monitored the electrical current and water pollution indicators over time. Later the aeration mode was changed and previous measurements of electricity generation, water pollution indicators were carried out, and compared with the previous stage. Results of the first mode of aeration have shown that the greatest value for Short Circuit Current (ISC) was (0.905) mA while the greatest value for Open Circuit Voltage (VOC) was (0.390) V. While a rise in current and voltage values was observed in the second mode of aeration, in which the greatest value of Short Circuit Current was (1.240) mA, and the greatest value of open circuit voltage (0.430) V. When the circuit has been connected to an external resistance R=100 Ω, the values for current, voltage, current density and power density were (0.805) mA, (0.084) V, (3.18) mA/m2, and (0.269) mW/m2, respectively. For water analysis, an increase in pH values of 8.90 was observed. The efficiency of removing of Chemical Oxygen Demand (COD), phosphates, nitrates and Total Dissolved Salts (TDS) has also increased, reaching: 72.11%, 62.70%, 35.60%, and 30.61%, respectively.